Growth performances and nutrient compositions of pabda Ompokbimaculatus (Bloch, 1797) grown in recirculating and closed aquaculture systems (Journal of the Asiatic Society of Bangladesh, Science, 2021)
This study evaluated the growth performances and nutrient compositions of pabda Ompok bimaculatus (Bloch, 1797) in a recirculating aquaculture system (RAS) and a closed aquaculture system (CAS). The average daily weight gain (ADG) and specific growth rate (SGR) of pabda in RAS (ADG: 0.18 g/d; SGR: 3.40 %/d) was 3.61- and 1.41-folds higher than that of the CAS (ADG: 0.05 g/d; SGR: 2.40 %/d). Fish had significantly higher level of PUFA (Poly-unsaturated fatty acid) in CAS (41%) than in RAS (33%). The ratio between omega-3 and omega-6 fatty acids in RAS and CAS were 0.73 and 0.69, respectively. This study’s results have demonstrated that the culture of pabda in RAS is more suitable than CAS in terms of growth.J. Asiat. Soc. Bangladesh, Sci. 47(1): 1-12, June 2021